ANALISIS PENGARUH INTERFERENSI WIFI TERHADAP QUALITY OF SERVICE (QOS) PADA MODEM WIRELESS HUAWEI EG8145V5 DENGAN METODE ACTION RESEARCH - Fahqi Juliansyah; Rinna Rachmatika (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Wireless networks have grown rapidly over the last two decades. In its use, wireless networks have drawbacks, one of which is susceptible to interference. Interference occurs because there are other wireless networks that work on the same frequency or channel in the same coverage area. Biznet is an ISP that provides wireless modem facilities to its customers, using the Huawei EG8145V5 wireless modem, but in practice there have been many reports of decreased network performance after being checked due to network interference. It is necessary to analyze the quality of wifi services using the action research method using QoS parameters based on TIPHON, namely, packet loss, jitter, delay and throughput. This was done by simulating two Huawei EG8145V5 modems with two test scenarios, and measured using the WireShark and NetSpot applications. This study shows the results of testing the second scenario, namely testing without being affected by wireless network interference, has a higher QoS value of 0.75 (93.75% of the index in the Very Satisfying category) compared to the results of the first scenario testing (affected by interference) which only reached index value 3 (only 75% of the index with the Very Satisfactory category)